Preserving biodiversity of the Ecudorian rainforest : basic healthcare, nutrition and parasitic control of common Amazonian animal species held at the model farm "Centro Fátima" - Riikonen, Annina; Kenic, Miriam (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2006)
This report contains information about housing, nutrition and medical management of some Amazonian animal species held at the model farm Centro Fátima. It is written as a handbook for the Center to help to promote good health and wellbeing of the animals living there.